Analysis of double‐Xi‐shaped millimetre‐wave patch antenna backed by a high‐order‐mode cavity using characteristic mode design - Feng, Botao; Chen, Junlong; Sim, Chow‐Yen‐Desmond (IET microwaves, antennas & propagation, 2021)
The authors propose an innovative double‐Xi‐shaped Chinese character artistic antenna backed by a high‐order‐mode cavity for 5G millimetre‐wave (mm‐wave) applications. The initial double‐Xi‐shaped microstrip antenna element is designed by using characteristic mode theory, and stable gain can be obtained across the whole 5G mm‐wave frequency band. By employing a slotted cavity with TE230 high‐order‐mode to excite 2×2 antenna subarray, a high gain of 13.2 ± 0.8 dBi and a high isolation better than 45 dB without additional feeding networks can be simultaneously achieved. To further improve the gain for reliable transmission, a 4×4 dual linearly polarised (LP) antenna array is also designed and fabricated. Measured results show that a wide frequency bandwidth of 11.45% (24.7–27.7 GHz) with a peak gain of 19.2 dBi and a high isolation of 33 dB is realised for the dual LP antenna array. The proposed method provides a simple and efficient prediction‐theory way to design artistic antenna for the first time, which solves the problem of designing specific‐shaped antenna without theoretical support.